Cleft and Craniofacial Clinic Formats in the United States: National and Institutional Survey. Issue 3 (May 2017) - Alleyne, Brendan; Okada, Haruko C.; Leuchtag, Randi M.; Rowe, David J.; Soltanian, Hooman T.; Becker, Devra B.; Lakin, Gregory E.
Abstract : Background: Craniofacial teams employ multidisciplinary clinics to optimize patient care. Different clinic formats exist among teams. Formats include providers rotating from room to room as separate specialties, patients rotating from room to room to either separate specialties or as 1 group, as well as providers rotating together as 1 group. Surveys were used to study family preferences between the different formats and to compare them with trends of national practices. Methods: Families of the authors' team clinic patients were surveyed from November 2012 to February 2013, after a clinic format change from patients moving between rooms to see providers, to providers moving between rooms to see patients. This survey focused on patient satisfaction, clinic format preference, and their perception of efficiency. A second, national survey was distributed to 161 American craniofacial teams approved by the American Cleft Palate–Craniofacial Association to survey clinic formats, provider satisfaction, and experience with other formats. Institutional survey data were tabulated as percentages and further analyzed using the Mann–Whitney Test. The national survey data was then tabulated and compared with authors' institutional results. Results: Thirty-nine of 54 (72.2%) families responded to the institutional survey. Providers moving between rooms were associated with greater patient satisfaction (mean 4.8 of 5, 5 being most satisfied) (0<0.0001), shorter perceived clinic time (76.9%), and an increased sense of comfort (84.6%). The difference in satisfaction rates was statistically significant ( P  <0.0001) between the primary clinic formats of providers rotating (mean of 4.8) and patients rotating (mean of 2.4). The national survey had 93 responses of 161 (57.7%). 54.9% of respondents have providers rotating between examination rooms, and 32.3% have patients moving between rooms. Other formats included the entire team moving as a group between rooms (10.8%) and specialties sitting together in 1 room while patients rotate (9.7%). Respondents were satisfied with current formats (mean 4.24 of 5, 5 being most satisfied). 22.2% had tried a different format previously. Conclusion: The most common American cleft and craniofacial clinic format is providers moving between rooms; however, all formats have high provider satisfaction. At our institution, patients prefer when providers move between rooms. Our study suggests that clinic formats do not need to be standardized, and the clinic format utilized should be tailored to the individual needs of the institution.